Os (des)caminhos das mulheres no teatro de Nelson Rodrigues: uma articulação entre o teatro e a psicanálise - Nascimento, Juliana Maria Girão Carvalho (2011)
This dissertation leans on some Nelson Rodrigues theater’s emblematic female characters, aiming to investigate these characters ways or un-ways, in order to understand the different expressions of female sexuality, as well as the fantasies and the subjective positions that rodriguean women take on living this sexuality and love. Considering the rodriguean theater’s virulence and the art’s power of giving expression to the unconscious creations, we suppose Nelson Rodrigues dramaturgy may carry important contributions on the psychoanalyst knowledge improvement about female sexuality. For that, this study has taken as analysis material the plays: Senhora dos Afogados(Lady of the Drowned), Vestido de Noiva (The Wedding Dress) and A Serpente (The Serpent. Based on Psychoanalysis theoretical references, Freudian concepts of unconscious, drive, repression, Oedipus complex, early Oedipus complex, castration complex, identification e superego were fundamental to guide this investigation; as well as the drama category action. The present research was bibliographic and sought, by the plays discourse analysis, to stick to the Rodrigues writing subtlety, as a sort of discourse transmitted by words and action. Thereby, Nelson Rodrigues theater’s women showed themselves, above all, rapt by passion and voluptuousness, in name of a “want” that exceeds desire and the meeting with the object; “want” also seems to lean on the shape of “another woman”, depository of an ambivalent love par excellence.